Penguatan Legalitas Produk Pangan Halal Pada UMKM Menuju Terwujudnya Ketahanan Pangan - Bambang Hermanu (Jurnal Agrifoodtech, 2023)
The improvement of food resilience in Indonesia, especially in the context of Micro, Small, and Medium Enterprises (UMKM) household industries, is a primary focus to achieve optimal food resilience. This write-up is a literature review related to the empirical phenomenon surrounding the issue of halal food products, discussing the strengthening of the legal aspects of halal food products in MSME household industries as a strategic step towards optimal food resilience. Halal food products are an essential need for Muslim communities, and government efforts to promote the halal industry align with the plan to become the world's halal industry center by 2024. The government has implemented policies to certify halal products through various agencies, such as the Technical Implementation Unit (UPT) of the Ministry of Industry and the Halal Product Assurance Organizing Agency (BPJPH) under the Ministry of Religious Affairs. The mandatory halal certification, starting with food and beverages in 2024, is a strategic step to strengthen the domestic industry's competitiveness in the global market. By reinforcing the legality of halal food products, it is expected to enhance consumer trust, develop the halal industry, and ultimately achieve optimal food resilience in Indonesia.